Pengaruh Sistem Informasi Akuntansi, Insentif, dan Motivasi Kerja Terhadap Kinerja Karyawan Pada PT Kimia Farma Apotek Unit Bisnis Denpasar - Ni Kadek Bagiani; Komang Krishna Yogantara; Gde Herry Sugiarto Asana (Jurnal Widya Akuntansi dan Keuangan, 2024)
Abstrac: The purpose of this research is to determine the influence of accounting information systems, incentives and work motivation on employee performance with the object PT KFA Denpasar. The research method used is a quantitative method with Purposive Sampling sampling technique. The total sample was 190 employees. This research uses multiple linear regression analysis using SPSS 23.00 tools. The results of the research show that (1) the accounting information system partially has a positive effect on employee performance at PT KFA Denpasar which is shown at a significance value of 0.027 which is smaller than 0.05, (2) the results of partial incentive testing have no effect on employee performance at PT KFA Denpasar (3) Test results on work motivation partially have a positive effect on employee performance at PT KFA Denpasar, (4) Accounting information systems, incentives and work motivation simultaneously have a significant effect on employee performance at PT KFA Denpasar. The influence of accounting information systems, incentives and work motivation on employee performance at PT KFA Denpasar is 21.3%, the remaining 78.7% is influenced by other variables not examined in the research. Keywords: Accounting Information Systems; Incentives; Work Motivation; Employee Performance